The effect of luteinizing hormone changes in GnRH antagonist protocol on the outcome of controlled ovarian hyperstimulation and embryo transfer - Jing-Shuang Zhou; Jian-Hong Chen; Fei-Fei Tang; Jian-Ping Ou; Xin Tao; Liu-Hong Cai (BMC, 2023)
Abstract Backgroud To investigate the effect of Luteinizing hormone (LH) level changes on the outcomes of controlled ovarian hyperstimulation (COH) and embryo transfer (ET) in gonadotropin-releasing hormone antagonist (GnRH-ant) protocol. Methods A total of 721 patients undergoing GnRH-ant protocol COH for the first IVF/ICSI cycles were retrospectively analyzed. COH process were divided into 2 stages, before (stage 1) and after (stage 2) the GnRH-ant initiation, and each with 5 groups basing on LH levels: LH decreased more than 50% (groups A1, A2), decreased 25-50% (groups B1, B2), change less than 25% (groups C1, C2), increased 25-50% (groups D1, D2), and increased more than 50% (groups E1, E2). Results There were no significant differences among groups of stage1 regarding COH and ET outcomes. For stage 2, the more obvious the decrease of LH level, the more the number of oocytes retrieved, mature oocytes, fertilized oocytes, embryos cleavaged and the numbers of embryo available (P < 0.05), but without significant differences regarding ET outcomes. We also found the freeze-all rate in Group A2 was higher (P < 0.001). Conclusion LH level changes before GnRH-ant addition were not related to COH and ET outcomes. LH level changes after the addition of GnRH-ant were related to the outcome of COH, and no significant differences were found relating to ET outcomes.